Mathematics in humanities - Szostek, Andrzej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
The topic of the article is the role of the mathematical education in the humanistic education (history, history of literature and art etc.). The author underlines the meaning understanding as the fundamental notion of the humanities. The lack of the understanding perspective leads the humanistic education to the superficial knowledge of facts and dates, always incomplete and not very useful for the grasping of the specific world of the human thinking and motivation. Mathematics, as the only pure formal subject in the Polish school educational program (there is no classes in logic in these schools), can provide the student at least with the three important abilities. Namely, mathematics education improves the imagination of the school-boys and girls (starting with the simple summing up and multiplication operations), deduction (as opposite to funding our convictions only on the opinions) and integrity of the knowledge (it is impossible to comprehend the more advanced mathematics theses with no knowledge of the other, more fundamental parts of it; much the same it is impossible e. g. to comprehend the essence of the historical processes without knowledge of the all important elements of them). However, what is needed in the school program in mathematics is some information about the more advanced mathematical theories and its applications to the other kinds of science (mathematics in cosmology, fractal theory, topology), These theories cannot be presented completely on this stage of education, yet can improve the imagination of the young men and help them to recognize the meaning of the mathematics for the understanding of the whole world, its structure and dynamism.